1969
DOI: 10.7164/antibiotics.22.399
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Fatty Acids From the Antibiotic Amphomycin

Abstract: From acid hydrolysates of amphomycin (+) 3-anteisotridecenoic acid, (+) 4-hydroxy-anteisotridecanoic acid lactone and 4-hydroxy-isododecanoic acid lactone were isolated. While the unsaturated acid is a genuine building component of the antibiotic, the lactones are formed from unsaturated acids during hydrolysis. * The authors express their gratitude to Mr. L. Szabo and H. Lundbeck & Co. of Copenhagen-Valby, Denmark, for the generous sample of amphomycin which made it possible to carry out such a detailed study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Epimerization domains are located at the ends of PstB and PstC in the modules 3 and 9, in accordance with the D configuration of pipecolinic acid and the Dab-9 amino acid residue. This result is consistent with the published stereochemical structure of the friulimicin and amphomycin peptides (7,48). PstD ends with a thioesterase domain for regiospecific cyclization.…”
Section: Resultssupporting
confidence: 81%
“…Epimerization domains are located at the ends of PstB and PstC in the modules 3 and 9, in accordance with the D configuration of pipecolinic acid and the Dab-9 amino acid residue. This result is consistent with the published stereochemical structure of the friulimicin and amphomycin peptides (7,48). PstD ends with a thioesterase domain for regiospecific cyclization.…”
Section: Resultssupporting
confidence: 81%
“…From acid hydrolysates of amphomycin, L-aspartic acid (3 mol), glycine (2 mol), L-rftreo-/3-methylaspartic acid,17 L-proline, L-valine, dpipecolic acid, w/z/-eo-a,/3-diaminobutyric acid,18 and D-eryí/iro-a,/3-diaminobutyric acid16 (1 mol each) were isolated and identified. 16 End Groups. Rearrangements.…”
Section: Methodsmentioning
confidence: 99%
“…24, 25 Subsequent studies of the structure of amphomycin indicated that its fatty acid and amino acid constituents were identical to those of glumamycin, and that aspartocin had the same amino acid content but different fatty acyl substituents. [45][46][47][48][49] This resulted in a proposal that most of the individual members of the amphomycin family contained the same amino acids in identical ratios and differed only in respect of their fatty acid constituents, which should be regarded as merely a consequence of the fermentation media and conditions used for their production. Complications in chromatographic characterization could also have arisen from facile transpeptidation reactions yielding b-aspartyl isomers due to the proximity of Gly and Asp residues in these molecules.…”
Section: Cyclic Peptidesmentioning
confidence: 99%